Detection of Hepatotoxicity by Non-Transferrin Bound Iron in Beta Thalassemia Major - Cheema, Asma Naseer; Khan, Dilshad Ahmed (International Journal of Pathology, 2018)
Background: Hepatotoxicity due to iron overload as a result of multiple transfusions along with concomitanthepatotropic infections has not been studied in detail.Objective: The objective of our study was to estimate the relationship between the extent of hepatocellularinjury as reflected by serum levels of alanine aminotransferase (ALT) and iron status indices likeFerritin and Non-transferrin bound iron(NTBI) .Materials & Methods: A total of 137 transfusion dependent thalassemic patients with median age of 10(range 3-21) years (73 males; 58 females) participated in the study. Total 76 (58%) patients were positivefor hepatitis B&C and 55 (42%) negative. Serum ALT and Aspartate aminotransferase (AST) weremore significantly raised in hepatitis positive patients in comparison to other thalassemics. Significantcorrelation was found between hepatocellular damage (raised ALT) and NTBI (r=0.305) in thalassemicpatients (figure. 3). No correlation was seen between serum ferritin and hepatocellular injury (r=0.028).We compared ROC curves of NTBI and Ferritin to detect hepatotoxicity (table 2). Serum NTBI provedto be better between the two. ROC curve of serum NTBI is shown (figure 4). Using cutoff value of1.75uM and with AUC of 0.81, serum NTBI can detect hepatocellular damage in beta thalassemia major(BTM) with 76%sensitivity and 88% specificity.Conclusion: A high percentage of thalassemic patients (58%) suffer from viral hepatitis after gettingtransfused. NTBI is the best measure of iron toxicity showing the good association with iron overloadcomplications as compared to serum ferritin.